Inclusão e educação: a construção e a relevância do projeto educativo comum na Rede Jesuíta de Educação - Pinto, Tatiana Vasconcellos (Universidade do Vale do Rio dos Sinos, 2025)
This article emerges from the intersection of listening, practice, and reflection. Rather than merely analyzing a document, it seeks to understand how the Common Educational Project (PEC), developed by the Jesuit Education Network, has contributed to making school a space where all students — with their histories, rhythms, and ways of learning — can feel seen, welcomed, and part of a whole. Drawing from the trajectory of the Society of Jesus and the construction of the PEC, the text invites reflection on how values deeply rooted in Ignatian spirituality — such as equity, respect for diversity, and genuine care for others — are embodied in daily school practices. The theoretical framework is based on authors such as Mantoan (2006), Pacheco (2010), Rubens (2016), Carvalho (2008), and Sündermann (2023), among others. The methodology follows a qualitative and exploratory approach. Data were collected through a questionnaire answered by three teachers from the 6th grade at Colégio São Luís, in São Paulo. Their generous and committed voices reveal concrete gestures of inclusion, as well as the limitations and challenges they face daily. Rather than offering answers, this research aimed to listen. And by listening, it became clear that inclusion is built in the details: in the extended time, in the deepened listening, in the effort to adapt, and in the desire to get it right — even when conditions are not ideal. The testimonies point to the need for more consistent support networks, continuous training, and school environments where care and co-responsibility are not exceptions but part of the living culture of the school. Ultimately, educating — in light of the PEC and Ignatian tradition — is also an exercise in humanity. When inclusion is carried out with authenticity, it ceases to be a task and becomes a way of being with others.
Keywords: Projeto Educativo Comum (PEC; Rede Jesuíta de Ensino (RJE); Inclusão escolar; Docência; Common Educational Project (PEC); Jesuit Education Network (RJE); School inclusion; Teaching practice